10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
Background The influence of sex on coronary inflammation in patients with non-obstructive coronary artery disease (CAD) remains unclear. This study aims to determine sex differences in coronary inflammation, quantified by pericoronary fat attenuation index (pFAI) derived from coronary computed tomography angiography (CCTA), and their impact on clinical outcomes among patients with plaque-positive non-obstructive CAD. Methods This study retrospectively included 1395 patients with plaque-positive non-obstructive CAD who underwent CCTA (61±10 years, 55.2% males). Major adverse cardiovascular events (MACEs) were defined as cardiac death, non-fatal myocardial infarction, rehospitalization for heart failure or unstable angina, and late revascularization. Results After a median follow-up of 85 months (interquartile range [IQR]: 72-99), 177 patients experienced MACEs. Male sex was independently associated with elevated coronary inflammation (pFAI > -70.1 HU; OR=1.36, P=0.047). Male patients had a significantly higher cumulative rate of MACE than female patients (P<0.001). Furthermore, patients with coronary inflammation (pFAI > -70.1 HU) exhibited significantly worse long-term outcomes than those without, and consistent findings were observed in both male and female subgroups (all P<0.001). In multivariable Cox regression analysis, pFAI remained independently associated with MACEs in patients with non-obstructive CAD (HR=2.33, P<0.001) and provided incremental prognostic value beyond clinical variables and traditional CCTA metrics (AUC: 0.683-0.781, P<0.001). Conclusion Among patients with plaque-positive non-obstructive CAD, males exhibited worse long-term outcomes than females and showed a stronger association with coronary inflammation. pFAI is independently associated with long-term prognosis and may enhances risk stratification in these patients.